2023
DOI: 10.1073/pnas.2217534120
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping anisotropic microgel particles in lipid membranes: Effects of particle shape and membrane rigidity

Abstract: Cellular engulfment and uptake of macromolecular assemblies or nanoparticles via endocytosis can be associated to both healthy and disease-related biological processes as well as delivery of drug nanoparticles and potential nanotoxicity of pollutants. Depending on the physical and chemical properties of the system, the adsorbed particles may remain at the membrane surface, become wrapped by the membrane, or translocate across the membrane through an endocytosis-like process. In this paper, we address the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…[110] Liu et al demonstrated that with the increasing aspect ratio of particles, it becomes more difficult for cell membrane to wrap the NPs, which partially explained the association between aspect ratio and internalization. [111] Shen et al found that the oblate ellipsoids are likely to contact cell membranes with its long edge, which might lead to difficulties for cells to swallow the NPs and resulting in incomplete wrapping. [112] Besides, the necessary orientation change for rod-shaped particles during wrapping requires increased energy consumption, which in contrast decreases its cellular uptake.…”
Section: Shape Of Ndcmentioning
confidence: 99%
“…[110] Liu et al demonstrated that with the increasing aspect ratio of particles, it becomes more difficult for cell membrane to wrap the NPs, which partially explained the association between aspect ratio and internalization. [111] Shen et al found that the oblate ellipsoids are likely to contact cell membranes with its long edge, which might lead to difficulties for cells to swallow the NPs and resulting in incomplete wrapping. [112] Besides, the necessary orientation change for rod-shaped particles during wrapping requires increased energy consumption, which in contrast decreases its cellular uptake.…”
Section: Shape Of Ndcmentioning
confidence: 99%
“…The adhesion of an NP with a uniform surface to a lipid membrane, resulting from attractive forces between the two, leads to the deformation of the membrane such that it conforms to the NP’s surfaces. Competition between the NP-membrane adhesive energy and the membrane’s curvature energy dictates the degree of wrapping of the NP by the membrane and induces an effective interaction between the NPs. This effective membrane-curvature-mediated interaction can be attractive and leads to NPs’ self-assembly on the membrane, as has been shown by numerous experimental and theoretical studies.…”
Section: Introductionmentioning
confidence: 96%
“…Various studies to date have investigated the role of different parameters influencing the wrapping process, such as particle size, , membrane asymmetry, , membrane tension and fluctuations, , local membrane curvature, , particle surface properties, and notably, particle shape. , Particle shape has attracted considerable attention given its impact on the bending free energy cost and potential to modify the engulfment pathway. For example, several theory and simulation studies predict that anisotropic particles, such as ellipsoids and rods, experience a spontaneous rotation during engulfment, a phenomenon that reduces the bending free energy cost. ,,, On the other hand, only a limited number of experimental studies have investigated the role of shape anisotropy in the wrapping process, for example, using DNA origami rods, microgel particles, or dumbbell particles with GUVs, gold nanoparticles with HeLa cells, and carbon nanotubes with mammalian cells . However, these studies are limited by using either nontunable and strong binding interactions (e.g., NeutrAvidin-biotin binding) or relatively small particles, ,, which makes tuning and following their membrane interactions at the single-particle level challenging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several theory and simulation studies predict that anisotropic particles, such as ellipsoids and rods, experience a spontaneous rotation during engulfment, a phenomenon that reduces the bending free energy cost. ,,, On the other hand, only a limited number of experimental studies have investigated the role of shape anisotropy in the wrapping process, for example, using DNA origami rods, microgel particles, or dumbbell particles with GUVs, gold nanoparticles with HeLa cells, and carbon nanotubes with mammalian cells . However, these studies are limited by using either nontunable and strong binding interactions (e.g., NeutrAvidin-biotin binding) or relatively small particles, ,, which makes tuning and following their membrane interactions at the single-particle level challenging. A detailed understanding of how rod-like particles interact with membranes during endocytosis not only is of fundamental interest but also has important toxicological implications.…”
Section: Introductionmentioning
confidence: 99%